2020
DOI: 10.3389/fnins.2020.00909
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Timed Sleep Restriction Attenuates LepRb-Mediated Signaling Pathways and Circadian Clock Gene Expression in the Rat Hypothalamus

Abstract: The sleep duration of adolescents has continued to decline over the past 20 years. Sleep insufficiency is one of the most important risk factors for obesity, but the mechanisms underlying the association are unclear. Therefore, the hypothalamic-regulated mechanisms of appetite and the circadian clock gene expression were examined in sleep-restricted rats. Rats aged 7 weeks were randomly divided into two groups: the control group and sleep restriction group (7 rats/group) rats were sleep-restricted for 4 weeks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Young rats sleep deprived also experienced an alteration of the genes involved in the transcriptional feedback loop regulated by CLOCK and BMAL1 proteins. All these events confirm that alteration of sleep length causes dysregulation of several pathways in the hypothalamus with consequences in the regulation of hunger and energy consumption [ 15 ].…”
Section: Sleep Deprivation Effects In Rat Modelsmentioning
confidence: 65%
“…Young rats sleep deprived also experienced an alteration of the genes involved in the transcriptional feedback loop regulated by CLOCK and BMAL1 proteins. All these events confirm that alteration of sleep length causes dysregulation of several pathways in the hypothalamus with consequences in the regulation of hunger and energy consumption [ 15 ].…”
Section: Sleep Deprivation Effects In Rat Modelsmentioning
confidence: 65%
“…After the 6-week CSD intervention, the bone formation and bone resorption makers were both significantly lower than in the NC group ( P <0.05), suggesting that CSD suppressed bone turnover status of growing rats, mainly affecting bone formation. Since the body weight has been shown to positively correlate with the bone loss, 16 the differences remained significant even after adjustment for covariates, weight.
Figure 2 Chronic sleep deprivation (CSD) leaded to bone remodeling imbalance in growing rats.
…”
Section: Resultsmentioning
confidence: 95%
“…Xue et al 15 found the expression level of protein p-AKT decreased significantly in the hippocampus with increasing inflammation and oxidative stress after 7 days of SD. Sun et al 16 also reported the reduced expression of IRS/PI3K/AKT/mTOR and FoxO1 signaling pathways in the hypothalamus of 4-week SD rats. Due to PI3K/AKT pathway reduced by SD, some drugs prevent the disorder induced by SD via activating this pathway.…”
Section: Discussionmentioning
confidence: 93%
“…In addition to circadian patterns of transcription factors and enzyme expression, the secretion of melatonin, insulin, glucagon, glucagon-like-peptide-1, cortisol, leptin, adiponectin, ghrelin, and RAAS is also coordinated by the molecular clock [ 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. All of these hormones are major regulators of metabolism, and therefore represent an important link between the circadian rhythm and metabolic processes [ 45 , 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: The Link Between Circadian Clock and Metabolismmentioning
confidence: 99%